2019
DOI: 10.1002/hbm.24827
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome is tied to dynamic brain states after mild to moderate traumatic brain injury

Abstract: The current study set out to investigate the dynamic functional connectome in relation to long-term recovery after mild to moderate traumatic brain injury (TBI). Longitudinal resting-state functional MRI data were collected (at 1 and 3 months postinjury) from a prospectively enrolled cohort consisting of 68 patients with TBI (92% mild TBI) and 20 healthy subjects. Patients underwent a neuropsychological assessment at 3 months postinjury. Outcome was measured using the Glasgow Outcome Scale Extended (GOS-E) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…However, human minds are not static but rather constantly switch between thoughts and cognitive states, and naturally, the connectivity patterns between brain regions fluctuate accordingly ( Hutchison et al, 2013 , Allen et al, 2014 , Calhoun et al, 2014 ). These fluctuations in functional connectivity are referred to as dynamic functional connectivity (dFC), and the entire network of dynamic connections throughout the human brain as the human ‘chronnectome’ ( Chang and Glover, 2010 , Calhoun et al, 2014 , van der Horn et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, human minds are not static but rather constantly switch between thoughts and cognitive states, and naturally, the connectivity patterns between brain regions fluctuate accordingly ( Hutchison et al, 2013 , Allen et al, 2014 , Calhoun et al, 2014 ). These fluctuations in functional connectivity are referred to as dynamic functional connectivity (dFC), and the entire network of dynamic connections throughout the human brain as the human ‘chronnectome’ ( Chang and Glover, 2010 , Calhoun et al, 2014 , van der Horn et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Put simply, these patterns can be thought of as prototypical functional connectivity patterns that subjects tend to return to across time ( Calhoun et al, 2014 ). Similar to other neurologic diseases, such as traumatic brain injury and stroke, it is plausible that changes in the dynamics of brain states are related to the etiology of FMD ( Bonkhoff et al, 2019 , van der Horn et al, 2019 ). Furthermore, it has been shown that in some cases different brain states transition between one another via cyclic patterns of connectivity increases and decreases ( van der Horn et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After PCA, group ICA was performed using the FastICA algorithm. The statistical reliability of independent components was assessed using the ICASSO method that validates the independent components via clustering the results of multiple ICA runs(Himberg, Hyvarinen, & Esposito, 2004); using this method, the component estimation was repeated 20 times. After group ICA, the Group information guided ICA (GIG-ICA) algorithm (Du et al, 2016; Du & Fan, 2013) in GIFT was performed to generate produce subject-specific images, enabling a comparison of both the time course and the spatial maps to evaluate between-group differences.…”
mentioning
confidence: 99%